Pengaruh Teknologi Digital dalam Pengelolaan Dokumen Crewchange di PT. Equinox Bahari Utama - Beniah William Oktavianus Yosey; Indah Ayu Johanda Putri; Dyah Ratnaningsih; Dian Junita Arisusanty; Faris Nofandi; Romanda Annas Amrullah (Universitas Veteran Bangun Nusantara, 2024)
Shipping companies ship agencies play an important role in representing the interests of ship owners in ports. In activities, the role of digital technology is very important to streamline and accelerate the process of managing ship crews and prospective crew documents to ensure safety, legal compliance, and smooth ship operations as necessary requirements during sailing. This study aims to determine the influence of Digital Technology in the Management of Crewchange Documents at Pt. Equinox Bahari Utama. The type of research used in this study is quantitative. This research was carried out at Sanur Port for 1 year. Pt. Equinox Bahari Utama. The population used in this study is employees of the Crewing Golar division and Cool Company Management USA, the crew of the ship who will make a crewchange with a sample of 45 respondents. The data sources in this study used primary and secondary data with data collection techniques, namely: questionnaires, observations, literature studies. The data analysis technique is the Simple Linear Regression test. The results of this study show that digital technology has a positive and significant influence on the management of crewchange documents at PT Equinox Bahari Utama. The magnitude of the positive influence of Digital Technology on the management of crewchange documents at PT Equinox Bahari Utama is 87%.